MODERASI SISTEM PENGENDALIAN INTERN PEMERINTAH PADA PENGARUH SAKD, SIMDA, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH - . Anggi; Yesi Mutia Basri; Rofika Rofika (Universitas Katolik Indonesia Atma Jaya, 2021)
This study aims to examine influence of the application of the Regional Financial Accounting System, the Regional Information Management System and the Competency of Human Resources on the Effectiveness of Regional Financial Management with the Internal Control System of the Government as the Varıabel Moderatıng. The population in this reserach are all employees who work at OPD Siak Regency, selected using purposive sampling technique. 92 respondents participated in this study . Data analysis techniques used in this study are multiple regression and moderate regression analysis (MRA).. The results of this study conclude: The application of regional financial accounting systems, regional financial management information systems, human resource competence affects the effectiveness of regional financial management. And the Government Internal Control System (SPIP) can moderate the implementation of regional financial accounting systems, regional financial management information systems and not for the competence of human resources on the effectiveness of regional financial management.